Pelanggaran Kode Etik Guru: (Studi Kasus : Dugaan Guru MAN Melakukan Asusila Terhadap Siswinya) - Kahar S. Laiya; Roy Marthen Moonti; Ibrahim Ahmad; Muslim A. Kasim (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2025)
Violation of the teacher's code of ethics is a serious problem that can damage the image of the education profession and endanger the school environment. This study focuses on a case study of a Violation of the Teacher's Code of Ethics by a teacher at MAN who was involved in alleged immoral acts against his female students. The purpose of this study was to explore the causes of the occurrence of the violation of professional ethics. The results of the study showed that factors of abuse of power, lack of supervision, and weak enforcement of the code of ethics contributed to the occurrence of the violation. The impact is very large, both for victims who experience physical and psychological trauma, and for the reputation of the educational institution itself. This study is expected to provide recommendations for improving supervision, ethics education, and stricter law enforcement in the educational environment to prevent similar incidents from happening again.